Tinjauan Etnografi terhadap Tradisi Bajapuik dalam Adat Minangkabau di Pariaman, Sumatera Barat - Aini, Nur; Suri, Nursukma; Pujiati, Pujiati (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2024)
This article aims to review the tradition of bajapuik in Minangkabau customs in Pariaman, West Sumatra through ethnographic study as an effort to anticipate the misinterpretation of this tradition as local cultural wisdom. The focus of this study is an analysis of the tradition where a woman proposes to a man for marriage, which is a distinctive feature in Pariaman and not generally applicable across the entire West Sumatra region. This ethnographic review elaborates on historical literature, cultural anthropology, and local documentation to further identify the roots and uniqueness of the bajapuik tradition. Additionally, this article seeks to explore the socio-economic factors influencing the evolution of the bajapuik tradition. The bajapuik tradition is not merely a formal ceremony but also reflects social, symbolic values, and mutual respect between both parties in the context of marriage. To preserve the sustainability of this culture and tradition, there is a need for collaboration between religious, customary, and cultural values in interpreting and respecting the practice of proposing to men.